Evaluation of Effectiveness and Benefits of iRAP and Bina Marga Methods for Road Safety Assessment on the Karanglo-Bts. Kota Batu (Karang Ploso) Segment - Devayanti, Shafira; Machsus, Machsus; Khoiri, Mohamad (Universitas Negeri Semarang, 2024)
According to Road Safety (2002), traffic accidents result from vehicles, humans, road environments, and their interactions. Addressing these issues is crucial for improving road safety, particularly for operational roads and those under maintenance, to prevent recurring accidents in the same locations. This study examines the effectiveness and benefits of two road safety assessment methods: the iRAP ranking analysis method and the Bina Marga ranking analysis method. The Karanglo–Batu City Border (Karang Ploso) road segment, spanning 7.99 km, was selected as the study area. Both methods analyze five key accident types: roadway departure, head-on collisions due to loss of control or overtaking, intersection accidents, and accidents at property access points. Factors influencing these accidents include probability, severity, operational speed, external traffic, and median traversability, with star ratings assigned based on the Star Rating Score (SRS). The iRAP method, utilizing the iRAP Demonstrator application, yielded an SRS score of 8.92 (3 stars), while the Bina Marga method, using manual calculations as per the Road Environment and Safety Guidelines Number 06/P/BM/2024, produced a score of 7.13 (3 stars). After implementing rehabilitation recommendations, both methods improved the score to 2.78 (4 stars). Effectiveness values were 35.68 for iRAP and 31.69 for Bina Marga, both categorized as effective. Post-improvement, the effectiveness value was 12.36, categorized as very effective. The iRAP method demonstrated higher direct benefits, particularly in data input, sampling, and implementation, making it more suitable for precise safety assessments.